Kepuasan Konsumen Di Kedai Nasi Kapau Uni Lis Bukittinggi - Satriyani, Rina; Chair, Ira Meirina; Syarif, Wirnelis (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2013)
Bukitinggi is one of destination tourism object for tourist. Which one of them that known by tourist nasi Kapu Uni LisBukittinggi. The background this research is 1) there are costumer problem that food product hadbeen over and is not be reiceive, 2) the serving is to long and slowly making costumer dissapointed, 3) the located of the place is not strategy, 4) having the more hight price from another nasi Kapau food shop, although having difference price but costumer didn’t choose to moving to another place. The research objective is to know the satisfaction costumer in the nasi Kapau Uni Lis food shop Bukittinggi include that quality of product and service.This research is description by using qualitative method. The instrument are collect files that used such as: interview, observation, and documentation, by using analisys model Milles and Hubberman files. The source files get from 10 people costumer and 1 waiter of nasi Kapau Uni Lis food shop. The result of analisys description show that the costumer didn’t satisfaction because the result of they are evaluation to showing the food product they are eating and the serviced they are reiceived is not good. To be increasing the customer selling valued they are need more product and service good quality. Keywords: product and service quality